Equity and sustainability in water-based ecotourism: An environmental justice perspective - Evio Tanti Nanita; Ansh Sharma (Institute of Advance Science, Social, and Sustainable Future, 2026)
Background: Water-based ecotourism is increasingly promoted as a pathway for sustainable local development, particularly in environmentally sensitive areas such as karst ecosystems. However, tourism expansion often prioritizes economic growth over ecological responsibility and moral accountability toward non-human nature. This study examines Paisupok Mirror Lake in the Banggai Islands as a case to explore how environmental justice in water-based ecotourism can be reframed through an eco-ethical perspective integrating social, ecological, and economic dimensions. Methods: The research employs a qualitative interpretive approach. It synthesizes secondary data from environmental assessments, policy documents, and previous field reports, complemented by primary insights from prior academic studies on Paisupok’s socio-environmental conditions. The analysis is theoretically grounded in deep ecology and Levinasian ethics of responsibility to reinterpret environmental justice within tourism governance. Findings: The study identifies three interconnected dimensions of environmental justice: distributive justice (equitable access to natural resources), participatory justice (meaningful involvement of local communities in tourism planning), and recognition justice (moral acknowledgment of ecological interdependence). The findings indicate that current tourism practices risk marginalizing ecological integrity unless ethical responsibility is embedded in governance frameworks. Conclusion: Sustainable water-based ecotourism requires a shift from purely economic orientation toward an eco-ethical governance model. Embedding moral responsibility within tourism planning is essential to safeguard the long-term resilience of fragile karst ecosystems and local community well-being. Novelty/Originality of this article: This study offers a novel conceptual synthesis by integrating deep ecology and environmental justice theory to formulate an Eco-Justice Tourism Framework. It advances ecotourism discourse by repositioning tourism not merely as an economic strategy but as an ethical practice grounded in ecological responsibility and social justice, particularly within developing and ecologically fragile contexts.